Access to Trifluoromethylketones from Alkyl Bromides and Trifluoroacetic Anhydride by Photocatalysis - Du, Hai‐Wu; Du, Yi‐Dan; Zeng, Xian‐Wang; Shu, Wei (Angewandte Chemie International Edition, 2023)
Aliphatic trifluoromethyl ketones are a type of unique fluorine‐containing subunit which play a significant role in altering the physical and biological properties of molecules. Catalytic methods to provide direct access to aliphatic trifluoromethyl ketones are highly desirable yet remain underdeveloped, partially owing to the high reactivity and instability of trifluoroacetyl radical. Herein, we report a photocatalytic synthesis of trifluoromethyl ketones from alkyl bromides with trifluoroacetic anhydride. The reaction features dual visible‐light and halogen‐atom‐transfer catalysis, followed by an enabling radical‐radical cross‐coupling of an alkyl radical with a stabilized trifluoromethyl radical. The reaction provides straightforward access to aliphatic trifluoromethyl ketones from readily available and cost‐effective alkyl halides and trifluoroacetic anhydride (TFAA).